Surface phytoplankton chlorophyll distribution continuously observed in the JARE-26 cruise (1984/85) to Syowa Station, Antarctica (SIBEX II) - Fukuchi, Mitsuo; Fukuda, Yasushi; Ohno, Masao; Hattori, Hiroshi (1986)
P(論文) A continuous measuring-recording system of surface chlorophyll α, which is equipped with a personal computer, was used in the 26th Japanese Antarctic Research Expedition (JARE-26) cruise of icebreaker SHIRASE to Syowa Station, Antarctica, in 1984-1985 as part of the Second International BIOMASS program. Geographical distribution of chlorophyll α observed on the southward leg through the eastern part of the Indian Antarctic Ocean in early-middle December and that on the northward leg through the western part of the Ocean in late February-early March coincided with the previous JARE observations. Comparing the data obtained on both legs, seasonal difference was also indicated; level of chlorophyll was high in December but low in February-March. Maximum concentration reached 1.55μg/ℓ in the north of the Antarctic Convergence in December. Variable, positive or negative relationships between temperature and chlorophyll α were observed in the zones of the Subtropical Convergence, Subantarctic Front and Antarctic Convergence. departmental bulletin paper